Religiosity in Qollana - Michaud, Andree (1970)
Firstly, I would like to mention the main characteristics of the community. The following are considered as Qollana people: a) The members of the nuclear families that have rights over the farmland, within the Qollana community itself; it doesn't matter if they currently live there or not. b) And that they consider themselves as belonging to the community.